2022
DOI: 10.1159/000521376
|View full text |Cite
|
Sign up to set email alerts
|

Internal Reliability and Validity of Copenhagen Burnout Inventory and Oldenburg Burnout Inventory Compared with Maslach Burnout Inventory among Nigerian Resident Doctors: A Pilot Study

Abstract: <b><i>Introduction:</i></b> Copyrighted Maslach Burnout Inventory (MBI) is perhaps the most widely used and validated tool in assessing burnout among different occupations and health care professionals compared to the free to use Copenhagen Burnout Inventory (CBI) and Oldenburg Burnout Inventory (OLBI). This study aimed to determine the reliability and validity of these tools in comparison with MBI among a subset of Nigerian resident doctors. <b><i>Methods:</i></b&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
3
10
0
1
Order By: Relevance
“…19 The strong positive correlation between CBI-PB and CBI-WRBO was equally similar to the findings from the pilot study. 19 This study found that only CPI-PB dimension could predict Oral health related quality of life amongst ECDs, the higher the CPI-PB score, the worse the OHRQoL. One would have expected the CBI-WRBO to also be a significant predictor, but this is not the case.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…19 The strong positive correlation between CBI-PB and CBI-WRBO was equally similar to the findings from the pilot study. 19 This study found that only CPI-PB dimension could predict Oral health related quality of life amongst ECDs, the higher the CPI-PB score, the worse the OHRQoL. One would have expected the CBI-WRBO to also be a significant predictor, but this is not the case.…”
Section: Discussionsupporting
confidence: 78%
“…18 Section 3 was on Copenhagen Burnout Inventory tool which had already been validated amongst early career doctors in Nigeria. 19 The final section was on the Oral Health Impact Profile (OHIP-14), a tool for assessing the oral health-related quality of life, which is a shortened form of the original OHIP-49. 20…”
Section: Methodsmentioning
confidence: 99%
“…It also hinders patient management. Different scales like the Oldenburg burnout inventory, burnout clinical subtype questionnaire, and Maslach burnout inventory (MBI) have been used previously for evaluating burnout among professionals (Demarzo et al, 2020;Gridwichai et al, 2020;Ogunsuji et al, 2022). In this study, CBI scales were used for evaluating burnout.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome variables included burnout, depression, and anxiety. Burnout was assessed using the Copenhagen Burnout Inventory (CBI) and Oldenburg Burnout Inventory (OLBI) [ 16 ]. The CBI consists of three sub-scales measuring personal burnout (6 items), work-related burnout (7 items), and client-related burnout (6 items) [ 11 ].…”
Section: Methodsmentioning
confidence: 99%